Named Entity Recognition on Tourist Destinations Reviews in the Indonesian Language - Hidayatullah, Ahmad Fathan; Putra, Muhammad Fakhri Despawida Aulia; Wibowo, Adityo Permana; Nastiti, Kartika Rizqi (Jurnal Linguistik Komputasional, 2023)
To find information about tourist destinations, tourists usually search the reviews about the destinations they want to visit. However, many studies made it hard for them to see the desired information. Named Entity Recognition (NER) is one of the techniques to detect entities in a text. The objective of this research was to make a NER model using BiLSTM to detect and evaluate entities on tourism destination reviews. This research used 2010 reviews of several tourism destinations in Indonesia and chunked them into 116.564 tokens of words. Those tokens were labeled according to their categories: the name of the tourism destination, locations, and facilities. If the tokens could not be classified according to the existing categories, the tokens would be labeled as O (outside). The model has been tested and gives 94,3% as the maximum average of F1-Score.